2011
DOI: 10.1177/1758834011428147
|View full text |Cite
|
Sign up to set email alerts
|

Sunitinib in advanced pancreatic neuroendocrine tumors: latest evidence and clinical potential

Abstract: Based on preclinical data available in the RIP1-Tag2 transgenic mouse model, sunitinib is an inhibitor of angiogenesis in pancreatic neuroendocrine tumors blocking vascular endothelial growth factor receptors and platelet-derived growth factor receptors in endothelial cells and pericytes, respectively. Evidence of objective response in phase I trials justified the initiation of a large phase II/III program using sunitinib in patients with advanced/ metastatic well-differentiated pancreatic neuroendocrine tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 53 publications
(120 reference statements)
0
28
0
Order By: Relevance
“…[7][8][9] Pyrrolic compounds continue to enter the pharmaceutical market and include molecules such as the receptor tyrosine kinase inhibitor sunitinib, approved in 2011 for the treatment of advanced neuroendocrine tumours of the pancreas. 7,10,11 Pyrroles also feature in a number of molecules presently undergoing preclinical trials such as lamellarin D, which is being investigated for its anticancer activity ( The synthesis of pyrroles can be achieved by a variety of reactions including the well documented Paal-Knorr condensation, first reported in 1884. 13 Despite the successful synthesis of pyrroles through this reaction a major limitation is introduced through the preparation of racemic diketone precursors for the condensation to form the M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 2 pyrrole core.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Pyrrolic compounds continue to enter the pharmaceutical market and include molecules such as the receptor tyrosine kinase inhibitor sunitinib, approved in 2011 for the treatment of advanced neuroendocrine tumours of the pancreas. 7,10,11 Pyrroles also feature in a number of molecules presently undergoing preclinical trials such as lamellarin D, which is being investigated for its anticancer activity ( The synthesis of pyrroles can be achieved by a variety of reactions including the well documented Paal-Knorr condensation, first reported in 1884. 13 Despite the successful synthesis of pyrroles through this reaction a major limitation is introduced through the preparation of racemic diketone precursors for the condensation to form the M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 2 pyrrole core.…”
Section: Introductionmentioning
confidence: 99%
“…If the tumor expresses more SSTRs than the surrounding tissue, the PRRT will be more effective; thus, SRS can predict the benefit of the treatment (low and high uptake indicate 20% and 60% chance of effect on liver metastases, respectively), and also the best results are observed in patients with good performance status and without major liver involvement (77). It is reported that RR and response duration are better with 177 Lu-DOTATATE therapy than 90 Y-DOTATATE therapy (20,78). Side effects of PRRT are hematological and/or renal toxicity, which are rare and usually mild.…”
Section: Peptide Receptor Radionuclide Therapymentioning
confidence: 97%
“…Sunitinib significantly prolonged PFS with 11.4 months compared with 5.5 months in the placebo group (HR 0.418, p=0.0001). Although median OS was not reached, sunitinib was favored by a HR 0.409 (p=0.0204), but with longer follow-up there was no statistical difference in OS (89,90). The FDA and European Medicines Agency (EME-A) have approved sunitinib for the treatment of unresectable or metastatic, well-differentiated PNETs with disease progression in adults (90,91).…”
Section: Sunitinib Malate (Sumentioning
confidence: 99%
“…It has been approved by the US Food and Drug Administration (FDA) and it has been tested in most of NETs in a phase III trial which resulted in an increase in patient progressionfree survival (Raymond et al 2011a, Delbaldo et al 2012.…”
Section: Vegf-targeted Therapy Angiogenesis In Pnets Andmentioning
confidence: 99%